Things in Poems - Hrdlička, Josef (Karolinum, 2022)
In this volume, fifteen scholars and poets, from Austria, Britain, Czechia, France, Germany, Ireland, Lithuania, and Russia, explore the topic of things and objects in poetry written in a number of different languages and in different eras. The book begins with ancient poetry, then moves on to demonstrate the significance of objects in the Chinese poetic tradition. From there, the focus shifts to things and objects in the poetry of the twentieth and the twenty-first century, examining the work of Czech, Polish, and Russian poets alongside other key figures such as Rilke, Francis Ponge, William Carlos Williams, and Paul Muldoon. Along the way, the reader gets an introduction to key terms and phrases that have been associated with things in the course of poetic history, such as ekphrasis, objective lyricism, and hyperobjects.
Keywords: Literární věda